Dissecting Stakeholder Participation in UN Human Rights Treaty Body Activities with Normative and Empirical Approaches: A Comparison of NGO and NHRI Participation - Hinako Takata (German Law Journal, 2024)
By addressing the question “Are the roles and values of stakeholder participation qualitatively different for non-governmental organizations (NGOs) and national human rights institutions (NHRIs), and if so, how?” this article dissects stakeholder participation in UN human rights treaty body activities. First, it normatively posits that stakeholder participation in treaty body activities carries three values, which weigh differently based on the actor and the treaty body activity concerned: facilitating “bounded” national deliberations, promoting international deliberations on human rights treaty standards, and supplementing the treaty bodies’ fact-finding capacity. It offers concrete normative guidance for treaty bodies on their engagement with NGO and NHRI participation to maximize the benefits of these values. It then empirically analyzes their current practice in light of the above-mentioned normative guidance. This article contributes, first, to the theorization of stakeholder participation in treaty body activities, which has been discussed but only in generalized or fragmented ways in previous studies. Second, it supports the effectiveness and legitimacy of treaty bodies by endorsing their practice that is consistent with the guidance and finding space for improvement. Finally, it provides a rationale for establishing and strengthening NHRIs by showing that NHRI participation has unique roles distinct from those of NGOs.